2006
DOI: 10.1002/ps.1260
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of anilinopyrimidine fungicides photoinduced by iron(III)–polycarboxylate complexes

Abstract: The photoinduced degradation of three anilinopyrimidine fungicides (cyprodinil, pyrimethanil and mepanipyrim) by Fe(III)-polycarboxylate complexes in aqueous solution was investigated. A photochemical redox reaction of Fe(III) complexes of oxalate and citrate occurs during irradiation (simulating sunlight) and is an important source of Fe(II) and a series of oxidants such as H2O2 and O radicals. The mechanism involves the formation of polycarboxylate radicals and/or carbon-centred radicals derived from decarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…Ozone can also undergo reaction with water to yield peroxide and hydroxyl radicals. The degradation of cyprodinil is probably an outcome of the attack at the nitrogen bridge between the two rings or the phenyl ring and/or the pyrimidyl ring by hydroxyl radicals formed from ozone [39] as typified in Figure 6 and further oxidation by Criegee mechanism.…”
Section: Figurementioning
confidence: 99%
“…Ozone can also undergo reaction with water to yield peroxide and hydroxyl radicals. The degradation of cyprodinil is probably an outcome of the attack at the nitrogen bridge between the two rings or the phenyl ring and/or the pyrimidyl ring by hydroxyl radicals formed from ozone [39] as typified in Figure 6 and further oxidation by Criegee mechanism.…”
Section: Figurementioning
confidence: 99%
“…The elemental composition of [TP1 + H] + is C 8 H 12 N 3 , and TP1 was characterized as 4‐cyclopropyl‐6‐methylpyrimidin‐2‐amine based on its CID mass spectrum. The corresponding TP has also been observed for pyrimethanil and mepanipyrim . TP1 loses either NH 3 from the form protonated on the amino function to give m/z 133, or NCNH 2 from the structure protonated on another nitrogen atom to give m /z 108.…”
Section: Resultsmentioning
confidence: 77%
“…UV photolysis processes are commonly used as an alternative to chlorine disinfection. Some efforts have been devoted to the direct and catalyzed photodegradation of pesticides, including identification of photoproducts, kinetic studies and reaction pathway establishment, in order to integrate these TPs into pesticide control procedures . These studies showed that photolysis, in combination with other techniques multiplying the number of degradation pathways, would target a large range of pollutants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many compounds are light sensitive, such as aldicarb, parathion, mecoprop, linuron, and chlorpyrifos (Burrows & Canle, 2002;Anfossi et al, 2006). Thus, it is necessary to study the effect of UV/Vis irradiation on the degradation rate of Plt.…”
Section: Degradation Of Plt 341 Effect Of Light Sourcementioning
confidence: 99%